Second Generation Nuclear-Weapon-Free Zone: Mixing Noble Ideas and Hard Reality - Umebayashi, Hiromichi (Mongolian Journal of International Affairs, 2011)
DOI: 10.5564/mjia.v0i14.24 Mongolian Journal of International Affairs No.14 2007 pp.58-63